Pengaruh Ukuran Kap, Opini Audit, Dan Profitabilitas Terhadap Auditor Switching(Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2010-2015) - Septyawan, Ary Hendra, Fauzan SE, M.si, CA, Ak (2017)
The purpose of this study was to examine the effect of the size of public accounting firm, audit opinion, and profitability on auditor switching. The research was conducted on manufacturing companies listed in Indonesia Stock Exchange 2010-2015 period. The population of the sample is manufacturing companies listed in Indonesia Stock Exchange 2010-2015 period. Determination of sample, using a purposive sampling method. The study had 126 samples from 21 companies. The data analysis was using multiple linear regressions analysis. The analysis showed that the size of public accounting firm affect the auditor switching. Audit opinion and profitability does not affect auditor switching. Key words : The size of public accounting firm, Audit opinion, Profitability, Auditor switching